Improving the efficiency of using capital at Bao Viet Group - Phan, Dinh Tam (Khoa Quốc tế, ĐHQGHN, 2020)
This paper focuses on analyzing, evaluating and offering solutions to overcome shortcomings, and to contribute to improve and bring better efficiency for using capital at Bao Viet Group in the period of 2016–2018. The researcher will study the system and theoretical basis of the organization of capital use, do research and evaluate the status of the organization of using capital in enterprises in general and the status of organization using capital at Bao Viet Group, and provide recommendations and basic conditions to improve the efficiency of capital use at the Bao Viet Group. The research uses following methods: Statistical methods, synthetic methods, analytical methods and comparison methods to clear the research objective. Thereby, the research recommends financial solutions: Adjust capital structure in a more reasonable way; Strict management and improve the profitability of capital in cash; Focus on investing in architectural houses, means of transmission and improving the efficiency of using existing fixed capital; Determine the Group's need for regular working capital appropriately; Regularly monitor, analyze and evaluate the efficiency of capital use; Periodically conduct financial analysis and evaluate the performance of the company, and needs to build and train high quality human resources.